Peran Masyarakat Dalam Pengelolaan Sampah Plastik Untuk Meningkatkan Kualitas Lingkungan Perkotaan Di Kelurahan Remu Utara Kota Sorong, Provinsi Papua Barat Daya - Murni; Slamet Widodo; Rahful A. Madaul; La Ibal (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Sorong city waste is a mixture of organic and inorganic waste. Based on the type of waste, Sorong City is divided into plastic, paper or cardboard, glass or bottles, metal or cans, B3, and organic waste. The survey results and direct measurements in the field show that Sorong Municipal Waste is also dominated by organic (51.37%) and plastic (17.12%) with densities of 286.0242 kg/m3 and 123.9438 kg/m3, respectively. To manage plastic waste, you can start by collecting it, selecting the type, flaking it, chopping it, and finally melting it. The method used in this service is a counseling method for the people of Remu Utara Village, Sorong City, who convey the role of the community in managing plastic waste to improve the quality of the urban environment. The results of this service are: (1) there is an increase in public awareness regarding the importance of processing plastic waste to maintain the quality of the urban environment by encouraging the community to actively participate in plastic waste management; (2) the community gains understanding in order to change people's behavior regarding the use and disposal of plastic waste. Society reduces the use of disposable plastics such as plastic bags, plastic straws, and plastic containers. Apart from that, the community also conducts waste segregation and reuse of plastic products to reduce the negative impact. Communities can carry out recycling of waste that can have economic value; and (3) the community is actively involved in plastic waste management activities, which can also collaborate with the local government to collect waste, conduct educational campaigns, and conduct environmental cleaning activities, as well as form a community concerned with waste.